Influenza A(H1N1) in pediatric patients with chronic co-morbidity - Aranda-Paniora, Franklin (2010)
Background: In July 2009, an outbreak of influenza A H1N1 was reported in the pediatric units of Instituto Nacional de Salud del Nino, Lima, Peru. Objectives: To determine the clinical features and evolution of hospitalized patients who presented influenza A(H1N1) virus infection and who also suffered chronic co-morbidity. Design: Retrospective clinical study. Setting: Instituto Nacional de Salud del Niño, Lima, Peru. Patients: Pediatric patients hospitalized at Medicine ‘D’ Service. Methods: We revised medical records associated with chronic comorbidity in all cases of influenza A H1N1 from July 1 through August 31, 2009. We describe clinical characteristics and evolution of hospitalized patients. Main outcome measures: Evolution and prognosis of the viral infection. Results: In the period of study 18 cases of influenza A H1N1 were confirmed in hospitalized patients. Twelve patients 2 to 17 year-old met inclusion criteria and in ten cases we considered the infection was acquired in the hospital. None of the patient required ventilatory support and all received respective oseltamivir treatment. Fever and cough were frequent and clinical resolution presented between the second and twenty fourth day of disease. Conclusions: There was no mortality in patients with co-morbidity treated with oseltamivir rate during the influenza A H1N1 outbreak in pediatric. Preventive measures, close surveillance and prompt medical treatment influenced in the evolution and prognosis of the viral infection.